The junior high school students' attitudes and self-efficacy towards science subjects - M. Dwi Wiwik Ernawati; Aulia Sanova; Dwi Agus Kurniawan; Yulita Dwi Citra (Jurnal Inovasi Pendidikan IPA, 2022)
This study was conducted with the aim of 1) knowing the attitudes and self-efficacy of students towards science subjects, 2) knowing the differences in attitudes that students have towards science subjects, 3) knowing the differences between students' self-efficacy towards science subjects, 4) knowing the differences in attitudes and self-efficacy of students, 5) knowing the relationship between students' attitudes and self-efficacy towards class science subjects. The type of research used in this research is a quantitative research type with the samples used are 74 students in 8th grade in Jambi. Through the results of data analysis, the results obtained are that 1) students' attitudes and self-efficacy towards science subjects are in the good to the excellent category, 2) there are differences in attitudes towards science subjects which is indicated by a significance value 0.05, 3) there are differences in students' self-efficacy towards science subjects which is indicated by a significance value 0.05, 4) there is a difference between attitudes and self-efficacy of students, 5) through correlation test it is known that there is a significant relationship between students' attitudes and self-efficacy towards science subjects.